The scale insects (Hemiptera: Coccoidea) of the Maltese Archipelago - Mifsud, David; Mazzeo, Gaetana; Russo, Agatino; Watson, Gillian W. (Zootaxa, 2014)
Past works on scale insects (Hemiptera: Coccoidea) from the Maltese Archipelago are reviewed. Based on the literature and contemporary collections, a total of 93 species of scale insects belonging to 12 scale insect families are here reported (Aclerdidae 1 species; Asterolecaniidae 4; Coccidae 17; Diaspididae 46; Eriococcidae 5; Kermesidae 1; Margarodidae 1; Micrococcidae 1; Monophlebidae 2; Pseudoccocidae 11; Putoidae 2 and Rhizoecidae 2). Of these, 17 species represent new distribution records. Ten species are excluded from the scale insect fauna of the Maltese Islands. Of the 93 species present, only 29 (31.18%) are probably indigenous and the rest (68.82%) represent established introductions from elsewhere. More than 65% of the indigenous species are typical Mediterranean in distribution, with a few species having a mainly European chorotype. A quarter of the established aliens originate from Eurasia, followed by an East Asian/ Oriental component (20.31%); European (14.06%); Neotropical (14.06%); cryptogenic (14.06%); African (7.81%) and Australasian (4.70%). Movement of live fruit trees and ornamental plants into the Maltese Archipelago from nearby countries is probably the main route for entry of alien scale insects into the country. Some possible future introductions are discussed.